If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -2 = 3y + -10 Reorder the terms: -2 + 7y = 3y + -10 Reorder the terms: -2 + 7y = -10 + 3y Solving -2 + 7y = -10 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -2 + 7y + -3y = -10 + 3y + -3y Combine like terms: 7y + -3y = 4y -2 + 4y = -10 + 3y + -3y Combine like terms: 3y + -3y = 0 -2 + 4y = -10 + 0 -2 + 4y = -10 Add '2' to each side of the equation. -2 + 2 + 4y = -10 + 2 Combine like terms: -2 + 2 = 0 0 + 4y = -10 + 2 4y = -10 + 2 Combine like terms: -10 + 2 = -8 4y = -8 Divide each side by '4'. y = -2 Simplifying y = -2
| 10=-15+5x | | X^2+2x+33=-3 | | 2x-x+3=9 | | in(x+5)=2 | | 1/2x+5=120 | | 7n-15=69 | | -(2+7x)= | | (x+15)(x+15)+5=50 | | 3(x-6)+4=30x | | 3(x-6)+4=20x | | 3x+x+0.67x=28 | | -15=-10-5x | | 3(x-6)+4=15x | | 5n-20=40 | | g=6f+h | | 26=4(u+6)-6u | | F(n)=2n-11 | | 50=4w+10 | | X+10=2x-50 | | -2x+(-28)=20 | | V=5k+t | | 4x-15=70 | | 12x^2+3x=17+x | | 8(k-5)+7k=-115 | | t(3t+19)=40 | | 5-7x=34 | | (x+6)(x-2)(x+3)=264 | | 3*5m-3= | | 4k-2k=-20 | | g=7f+h | | x+5=2y-20 | | y=-3x^4-18x^3-24x^2 |